Mathematical micromodeling of infilled frames: State of the art - Asteris, Panagiotis G.; Cotsovos, D.M.; Chrysostomou, Christis; Mohebkhah, A.; Al-Chaare, G.K. (My University, 2013)
The in-plane contribution of infill walls on the structural response of infilled frame structures is an important problem and many research initiatives, via experimental and numerical methods, have been conducted in order to investigate it thoroughly. As a result, the need to consider these research findings on the structural performance has been acknowledged in the latest generation of structural design codes. However, due to the uncertainties concerning the behavior of masonry at the material and structural level, these elements are usually ignored during practical structural analysis and design. They are overtly considered only when there is suspicion that their influence is detrimental to the overall structural response or to the behavior of individual load bearing elements or when it is necessary to justify an improvement in the overall load-carrying capacity or structural performance in general. In this paper, a thorough overview of the different micromodels proposed for the analysis of infilled frames is presented, and the advantages and disadvantages of each micromodel are pointed out (this paper follows our recent review paper on the state-of-the-art of the mathematical macromodeling of infilled frames, thus completing the overview of both macro- and micro- models in the field). Practical recommendations for the implementation of the different models are also presented.
Keywords: Discrete element method; Finite elements; Infilled frames; Interface elements; Masonry; Nonlinear analysis; United States of America